Factors Affecting Interest In Using E-Commerce And E-Wallet With Using Technology Acceptance Model - Fitranita, Vika; Zoraya, intan; Wijayanti, Indah Oktari (UNIB Press, 2023)
This study aims to determine the Influence of Interest in Using an E-Commerce-Based Accounting Information System and the interest of OVO customers using the Technology Acceptance Model (TAM). Data collection was carried out by giving questionnaires to respondents using OVO and Tokopedia in Bengkulu City. The sample in this study were 215 respondents using OVO and Tokopedia. Measurement of data in this study using Multiple Regression analysis with analysis tools using data processing software Eviews 12. In this study used data quality test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis and hypothesis testing. The results of the study show that the ease of use variable has no effect on interest in use, the variables perceived usefulness, trust, attitudes towards use are significantly positive on interest in use, risk variables have a significant negative effect on interest in use